The effectiveness of monetary policy during the recent financial turmoil - Puriya Abbassi; Tobias Linzert (Verein für Socialpolitik, 2010)
The recent financial crisis has deeply affected money markets. We analyze the effectiveness of monetary policy in the euro area with respect to (i) how much monetary policy expectations are reflected in money market rates, (ii) how much money market rates were disturbed by liquidity and credit risk, and (iii) the impact of extraordinary central bank measures on money markets. We find that market's expectations are less relevant for money market rates up to 12 months after August 2007. At the same time, the ECB's additional liquidity provision through longer-term refinancing operations account for at least a 60 basis point decrease in Euribor rates.
Keywords: E43; E52; E58; 330; Monetary transmission mechanism; Financial Crisis; Monetary policy implementation; European Central Bank; Money market